Dietary adherence to the Mediterranean diet pattern in a randomized clinical trial of patients with quiescent ulcerative colitis - Haskey, Natasha; Shim, Rachel C. K.; Davidson-Hunt, Alexander; Ye, Jiayu; Singh, Sunny; Dieleman, Levinus A.; Jacobson, Kevan; Ghosh, Sanjoy; Gibson, Deanna L. (Frontiers in Nutrition, 2022)
Background: The Mediterranean diet pattern (MDP) is believed to improve health and promote balanced inflammation and metabolism. While unknown, compelling evidence suggests that MDP could benefit patients with inflammatory bowel disease (IBD). We aimed to evaluate the level of diet adherence, diet quality and nutritional adequacy of the MDP in patients with Ulcerative Colitis (UC). Methods: Adult participants (n=32) with quiescent UC were randomized to follow a MDP (n=18) or Canadian Habitual Diet (CHD) (n=14) for 12 weeks. The MDP participants received tailored nutrition education from a Registered Dietitian. Demographic, clinical data, medical history, and quality of life were assessed with the Short Inflammatory Bowel Disease Questionnaire (SIBDQ), dietary adherence with the Mediterranean Diet Serving Score (MDSS), diet quality via the Healthy-Eating Index-2015 (HEI-2015) and dietary intake (ASA-24) were completed at baseline and week 12. Results: Participants’ diets were analyzed (MDP n=15, CHD n=13). The MDP (n=10, 67%) achieved a high level of adherence (MDSS score between 16-24) versus CHD (n=3), (p=0.030). HEI-2015 significantly increased from baseline to week 12 (p=0.007) in the MDP and was significantly higher at week 12 compared to the CHD (p=0.0001). The SIBDQ (bowel domain) showed reductions in the passage of large amounts of gas (p=0.01) and improvements in tenesmus (p=0.03) in the MDP. Despite enhanced diet quality and adherence in the MDP, females had inadequate intakes of calcium, iron, vitamin D, vitamin E, and choline and males had inadequate intakes of fibre, vitamin D, vitamin E and choline. No adverse events were reported. Conclusions: With nutrition education, high adherence to the MDP was achieved without an increase in bowel symptoms. Following the MDP led to a higher diet quality; however, nutritional inadequacies were identified. Tailored dietary education focusing on nutrients of concern when following the MDP is recommended to ensure nutritional adequacy. Clinical Trials NCT03053713. Registered 02 February 2017, https://clinicaltrials.gov/ct2/show/record/NCT03053713